Untangling some taxonomic riddles on damselfly genera (Zygoptera) from the neotropical region - Von Ellenrieder, Natalia (2007)
Examination of type material deposited in the IRSNB (Royal Belgian Institute of Natural Sciences, Brussels, Belgium) and in the BMNH (British Museum of Natural History, London, Great Britain) allowed us to solve taxonomic riddles regarding several damselfly (Zygoptera) genera from the neotropical region. We provide notes on the status of several types, and introduce the following new synonymies: Argia huallaga Fraser, 1946 = A. adamsi Calvert, 1902; Argia makoka Fraser, 1946 = A. kokama Fraser, 1946; Argia mollusca Fraser, 1946 = A. collata Selys, 1865; Argia trifoliata Fraser, 1946 = A. variegata Förster, 1914; Argia umbriaca Fraser, 1946 = A. indicatrix Calvert, 1902; Amphiagrion amphion Selys, 1876 = Ischnura verticalis (Say, 1840); a new combination: Oxyagrion cardinalis Fraser, 1946 to Leptobasis cardinalis (Fraser, 1946); and three lectotype designations (for Acanthagrion gracile race? lancea Selys, 1876, Acanthagrion trimaculatum Selys, 1876, and Leptagrion flammeum Selys, 1876).